The development, manufacture and evaluation of sustained release gastric-resistant isoniazid and gastroretentive microporous rifampicin microspheres - Mwila, Chiluba (Rhodes University, Faculty of Pharmacy, Pharmacy, 2018)
According to the World Health Organization Global Tuberculosis (TB) 2017 Report, there were an estimated 10.4 million new TB cases worldwide of which, in 2016, 65 % occurred in men, 28.1 % in women and 6.9 % in children. TB is the ninth leading cause of death globally and is the leading cause due to an infectious organism surpassing HIV/AIDS. Treatment is long-term and the use of a combination of medicines is required for success. The concern related to the use of fixed dose combination products for the treatment of TB is the issue of low bioavailability of rifampicin observed from a number of fixed dose combination (FDC) formulations. The hydrolysis of rifampicin, in acidic media, to form insoluble 3-formyl rifamycin SV contributes to poor bioavailability of rifampicin. The degradation of rifampicin to form this poorly absorbed compound is accelerated in the presence of isoniazid via the reversible formation of isonicotinyl hydrazone is a further factor contributing to the poor bioavailability of rifampicin. Therefore, the development of a novel drug delivery technology that prevents interactions between rifampicin and isoniazid in an acidic medium is required. A Box Behnken design was successfully used for the optimisation of a rapid and accurate stability-indicating gradient elution RP-HPLC method for the simultaneous analysis of isoniazid, pyrazinamide and rifampicin. The method was validated using ICH guidelines and the results indicate it can be used for the rapid analysis of commercially available TB FDC formulations containing the active pharmaceutical ingredients, API. The method is precise, sensitive and has the necessary selectivity for use during formulation development and optimisation studies for a combination of rifampicin, isoniazid and pyrazinamide. Initially formulation activities were undertaken with rifampicin and isoniazid for the development of an approach to enhance the effective delivery of these compounds. The characterisation of rifampicin and isoniazid was undertaken using spectroscopic, thermal and microscopic analysis. The studies revealed that the compounds are crystalline and exhibit distinct characteristic sharp peaks in X-ray diffractograms and Differential Scanning Calorimetry thermograms. The thermograms, 13C Nuclear Magnetic Resonance and Fourier Transform Infrared spectroscopy results identified that rifampicin occurs as the form II polymorph however, as there are no significant biopharmaceutic differences between the polymorphic forms of rifampicin this information was used for identification purposes only. The results were used as baseline data for comparative purposes to monitor changes that may occur when rifampicin and isoniazid are used in formulation development, dosage form manufacture and characterisation activities for a FDC technology designed to deliver both compounds simultaneously. Hydroxypropylmethylcellulose acetate succinate (HPMC-AS) and EudragitÂ® L100 polymers were successfully used for manufacture of isoniazid loaded gastric-resistant sustained release microspheres using an o/o solvent emulsification and evaporation approach. A Hybrid experimental design was used to investigate the influence of input variables viz., homogenisation speed and amount of HPMC-AS and EudragitÂ® L100 on gastric-resistance, INH release and encapsulation efficiency. The approach of using coating polymers viz., HPMC-AS and EudragitÂ® L100, to manufacture gastric resistant sustained release microspheres of isoniazid is unique and was efficient for preventing the release of isoniazid in an acidic environment. Only 0.523 % isoniazid was released from the optimised formulation after 2 h exposure to pH 1.2 0.1 M HCl suggesting there is also the possibility of minimising the accelerated degradation of rifampicin that occurs in the presence of isoniazid in acidic media. The microspheres also exhibited sustained release properties without burst release in pH 6.8 0.1 M phosphate buffer as < 5 % isoniazid was released at 0.5 h and only 11 % isoniazid was released at 2 h. The release of isoniazid was sustained over the entire period of dissolution testing with > 85 % isoniazid released at 24 h, implying that the majority of encapsulated isoniazid would be available for absorption. The manufacturing process resulted in the production of hard spherical particles and particle size analysis revealed that the microspheres ranged between 415.76 Â± 76.93 Î¼m and 903.35 Â± 197.10 Î¼m in diameter. The microspheres exhibited excellent flow properties attributed to the spherical nature of particles. Carr"Ÿs index (CI) was 4.934 Â± 0.775 % and the Hausner ratio (HR) was 1.148 Â± 0.033 indicating good packability of the microspheres that would help in achieving weight and content uniformity of capsule dosage units. The manufacturing process however produced a low % yield suggesting that scale up difficulties may be encountered. However the high encapsulation efficiency observed may counter the challenges associated with the low yield. The DSC thermograms and FT Raman spectra of 1:1 mixtures of isoniazid, excipients and the microspheres did not reveal any potential detrimental interactions. Microporous floating sustained release microspheres for the delivery of rifampicin in the stomach have been successfully manufactured using emulsification and a diffusion/evaporation process. A novel approach using solvent mixture of acetone and dichloromethane that has not been reported for the manufacture of rifampicin microspheres was successfully used and resulted in the formation of a stable emulsion and the manufacture of rifampicin-loaded microspheres with uniform characteristics. In addition the manufacturing process was shorter than most other reported methods. A Box-Behnken experimental design was successfully used to study the influence of ethylcellulose, EudragitÂ® RLPO and d-glucose content on the floating properties, encapsulation efficiency and % yield of microspheres. The optimised formulation did not yield desired floating characteristics as the % buoyancy was low and floating lag times were high. The optimised formulation was modified by addition of NaHCO3 to increase the % buoyancy and reduce the floating lag time. Rifampicin release from the microspheres of the modified batch was 87.10 % at 12 h and the microspheres exhibited a % buoyancy of 87.66 Â± 1.28 % (n = 6) and floating lag time of 15 Â± 3.2 (n = 6) seconds. The microspheres remained buoyant for up to 12 h and an encapsulation efficiency of 88.26 Â± 1.25 % was achieved. SEM images of microspheres following exposure to dissolution fluid revealed that the microspheres had numerous pores on their surface. The mean particle size distribution ranged between 423.19 Â± 121.86 Î¼m to 620.07 Â± 102.67 Î¼m. The microspheres exhibited similar flow characteristics to isoniazid microspheres with a CI of 1.422 Â± 0.074 %, and HR of 1.034 Â± 0.002. The excellent flow characteristics indicate that filling of the microspheres into hard gelatin capsules was unlikely to pose a challenge in respect of producing a product with uniform content. Rifampicin-excipient compatibility studies did not reveal any potential or significant interactions suggesting that the excipients used for the manufacture of the microspheres were compatible, although long term stability studies would be required to ascertain this is, indeed the case. The microporous floating sustained release microspheres manufactured in these studies has the potential to increase the bioavailability of rifampicin as they may be retained in the stomach where the solubility of rifampicin is high and from which absorption is best achieved. The degradation of rifampicin after 12 h dissolution testing in pH 1.2 0.1 M HCl in the presence of isoniazid gastric-resistant sustained release microspheres was only 4.44%. These results indicate that the degradation of rifampicin in the presence of isoniazid in acidic media can be overcome by encapsulation of both active pharmaceutical ingredients in a manner that ensure release in different segments of the gastrointestinal tract. The use of sustained release microporous gastroretentive rifampicin microspheres in combination with sustained release isoniazid gastric-resistant microspheres revealed that accelerated degradation of rifampicin in the presence of isoniazid is reduced significantly when using this approach and a FDC of rifampicin and isoniazid microspheres has the potential to improve the bioavailability of rifampicin thereby enhancing therapeutic outcomes. In vivo studies would be required to confirm the potential benefits of using this approach to deliver rifampicin in combination with isoniazid.,Thesis (PhD) -- Faculty of Pharmacy, Pharmacy, 2018
Keywords: Biodegradation; Microspheres (Pharmacy); Drug delivery systems; Rifampin; Isoniazid